Elucidating the Connection Between the Health-Promoting Properties of Limosilactobacillus fermentum Lf2 and Its Exopolysaccharides - Elisa C. Ale; Analía Ale; Guillermo H. Peralta; José M. Irazoqui; Gabriela Correa Olivar; Victoria Allende Roldán; Gabriel Vinderola; Ariel F. Amadio; Carina V. Bergamini; Jimena Cazenave; Ana G. Binetti (Fermentation)
The potential probiotic properties of Limosilactobacillus fermentum Lf2, an exopolysaccharide (EPS)-producing strain, were assessed in C57BL/6 mice. The aim of this work was to elucidate if these properties could be associated with the ability to produce EPSs. Mice were divided into three treatments: L (mice treated with Lf2), E (animals that received EPSs), and C (control group). The levels of fecal acetic and propionic acids significantly increased in L and E compared with C. Catalase activity increased in L in comparison with the other groups in the liver and small intestine. The enzyme activities of superoxide dismutase and glutathione S-transferase increased in the large intestine for L compared with C. In addition, in the large intestine, the concentration of TNF-α was reduced in L and E in comparison with C. In the small intestine, TNF-α, IFN-γ, IL-12, and IL-6 presented lower levels in L and E than C. The analysis of the gut microbiota showed that L presented higher levels of Peptococcaceae and Rikenellaceae, while E had higher levels of Peptococcaceae than C. Overall, these results provide new insights into the relationship between the probiotic properties of lactic acid bacteria and their ability to produce EPSs.